An interesting case of disseminated tuberculoma of brain and spinal cord - Parameshwar Keerthi B H; Anil Kumar Sakalecha; Varun S; Shivaprasad G Savagave; Raveesha Raveesha (Journal of Clinical and Biomedical Sciences)
Tuberculosis is a public health problem worldwide causing significant morbidity and mortality. Manifestations of tuberculo-sis are widely classified as pulmonary and extra pulmonary. Tuberculoma is one of the CNS manifestations, which on imag-ing shows ring enhancing lesions. Although intracranial tuberculomas are common, spinal tuberculomas are rare and consti-tute only 2% of CNS tuberculomas. We present a case of both intra-axial and spinal tuberculoma in the same patient. Keywords: Tuberculosis, CNS, Tuberculoma, Ring enhancing lesion, MRI